Novel boride-enhanced solar salts: Thermophysical and structural properties for thermal energy storage - Gurgenc, Ezgi; Öztop, Hakan Fehmi; Yamac, Halil Ibrahim; Canbay, Canan Aksu; Senocak, Safak Melih; Ozabaci, Murat; Gur, Muhammed (Elsevier, 2026)
Molten nitrate salts, widely used as thermal energy storage (TES) media in concentrated solar power (CSP) systems, suffer from intrinsic drawbacks such as low thermal conductivity, moderate thermal stability, and limited heat capacity. Conventional oxide nanoparticles have been explored to mitigate these limitations, yet their improvements are often restricted by relatively low intrinsic conductivity and stability. In this context, boride-based nanoparticles (HfB2, TiB2, and ZrB2) have attracted increasing attention owing to their exceptional thermal conductivity, chemical inertness, and high-temperature stability. In this study, solar salt (60 wt% NaNO3-40 wt% KNO3) was modified with different weight fractions (0.5-2.0 wt%) of HfB2, TiB2, and ZrB2 nanoparticles, and their thermophysical properties were systematically investigated. The results revealed that boride addition significantly enhanced density, specific heat capacity (Cp), thermal conductivity, and thermal stability compared to pure solar salt. Specifically, Cp increased from 1.51 J/g.K (pure salt) to 2.68 J/g.K with 2 wt% HfB2 (77.8 % increase), while ZrB2 and TiB2 yielded 2.39 J/g.K (58.4 %) and 1.60 J/g & sdot;K (6.2 %), respectively. Thermal conductivity rose from 0.632 W/m.K (pure salt) to 1.53 W/m.K (HfB2), 1.60 W/m.K (TiB2), and 1.38 W/m.K (ZrB2) at 2 wt% loading. TGA confirmed improved decomposition stability, with TiB2 showing the highest thermal stability at 651 degrees C. Additionally, density measurements indicated systematic increases with additive concentration, with the highest value (2.2411 g/cm3) recorded for ZrB2 at 2 wt%. These findings demonstrate that boride nanoparticles, even at relatively low concentrations, can effectively enhance the thermophysical performance of solar salt, surpassing many conventional oxide-based additives. Among the additives, HfB2 is most promising for maximizing energy density, TiB2 for high-temperature stability and conductivity, and ZrB2 for balanced multipurpose performance. Such improvements highlight the potential of boride-based nanocomposite salts for next generation CSP and thermal energy storage applications, particularly in hightemperature operation regimes where both energy density and efficient heat transfer are critical.
Keywords: Solar salt; Thermal energy storage; Metal borides (HfB 2; TiB 2; ZrB 2 ); Specific heat capacity; Thermal conductivity; Concentrated solar power